The “Psychology” of organ donation: two exploratory studies considering Italian “Health professionals” and “Citizens” - Franca Paola Severino; Andrea Guazzini; Laura Rasero; Stefano Bambi; Guya Piemonte; Samuele Baldassini Rodriguez (Infermieristica Journal)
Background: Transplantation extends and improves lives, but the shortage of organs is one of the main factors limiting the number of transplants in Italy. Objectives: The aim of this research was to understand the psychological and socio demographic determinants that can be related to the manifestation of the willingness to donate in a sample of citizens and professionals. Methods: In the study conducted on two samples (health professionals and citizens), two self-administered questionnaires were created ad hoc and administered to the participants recruited by means of a snowballing not-randoming procedure. Results: 386 citizens and 122 health professionals completed the questionnaire. Results frequently supported the literature. Specifically, with reference to the sample of citizens, (a) women are more likely to express a willingness to donate than men; furthermore, (b) having a realistic knowledge of the topic has a relationship with this manifestation. In both samples, (c) having previously discussed the topic of donation is relevant to expressing willingness to donate. With reference to the sample of professionals only, (d) having received training on organ donation has a relationship with practitioners' willingness to donate. Conclusion: There are several factors that influence the manifestation of willingness to donate in both samples. Efforts should be stepped up to provide comprehensive and appropriate education, knowledge and training on the subject to increase willingness to donate.